Patient-physician communication in health centers: A qualitative study - Mehran Alijanzadeh; Mohammadreza Maleki; Hamid Pourasghari (Wolters Kluwer Medknow Publications, 2023)
Introduction: A good relationship between physician and patient is effective in improving public health. The present study aimed to identify the factors affecting proper patient-physician communication in health centers. Methods: To this end, an exploratory qualitative study was conducted in 2019. The interviews were performed purposefully, and 18 patients referred to health centers were interviewed with maximum variation. The data were collected using semi-structured interviews and were analyzed using the approach of content analysis. Results: Data analysis revealed two main themes of human communication and health access. The theme of human communication consisted of four subthemes: physician's knowledge and experience, physician's behavior and ethics, comprehensive attention to the patient, and physician's discipline. Further, the theme of health access consisted of two subthemes: the physical condition of the center and the condition of the equipment. Conclusion: The identified components can be used to train medical students and evaluate the communication performance of doctors in health centers paying appropriate attention to these factors leading to patient satisfaction and, consequently, improving public health.